Blade [videorecording (Blu-Ray)] - Norrington, Stephen, 1964-; Snipes, Wesley; Kristofferson, Kris; Dorff, Stephen, 1973-; Wright, N'Bushe, 1970-; Logue, Donal, 1966- (Distributed by Warner Home Video : New Line Home Entertainment, 2012)
When the bloodthirsty immortals' lord declares war on the human race, half-vampire Blade is humanity's last hope for survival.